The Relationship Between Emotional Intelligence, Academic Procrastination, and Adolescent Mental Health at SMK Muhammadiyah 5 Al Furqan - Meilany, Vinchen Bintang; Lisnawati, Ica; M. Syafwani; Raya, Mardha (Papua Medicine and Health Science, 2025)
Adolescence is a developmental phase that is complex and full of challenges, encompassing cognitive, affective, and social behavioral aspects. One crucial factor that supports adolescents' adaptive abilities in coping with such pressures is emotional intelligence. Individuals with strong emotional intelligence tend to manage emotions effectively, build harmonious relationships, and demonstrate resilience to stress. On the other hand, academic procrastination is a common behavior among adolescents, often stemming from poor time management, fear of failure, and low motivation, which ultimately negatively impacts academic performance and mental health. This study aims to examine the relationship between emotional intelligence, academic procrastination, and adolescent mental health at SMK Muhammadiyah 5 Al Furqan. A quantitative approach with a cross-sectional design was employed, involving 90 respondents selected through systematic random sampling. Data were analyzed using univariate and bivariate analyses with the Spearman rho correlation test. The results revealed a significant negative relationship between emotional intelligence and academic procrastination (p = 0.004; r = -0.304), as well as a strong negative relationship between emotional intelligence and adolescent mental health problems (p = 0.000; r = -0.662). Conclusion: The higher the emotional intelligence of adolescents, the lower their tendency to engage in academic procrastination, and the better their mental health condition.